Sulla definizione del paesaggio agrario in età moderna, con particolare riferimento al caso meridionale - Barbagallo, Salvatore (Études sur la Région Méditerranéenne, 2022)
The agricultural landscape expresses the characteristics of the process of anthropization in the territory. The visible signs of these transformations can be inferred from various sources such as maps, cadastral surveys and, last but not the least, pictorial sources. It was Emilio Sereni in the History of the Italian agricultural landscape who also used artistic iconography to reconstruct some models of landscape development and outline the types of environmental frameworks for specific reasons. This process of anthropization, and therefore of landscaping remodeling, naturally also affects demographic development, climate change, the characteristics of society and economic relations.